Transparency and Accountability in School Financial Management: A Study of Informal Fundraising for Teacher Retirement Events (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2026)
Purpose of the study: This study aims to critically examine the practice of informal fundraising in public schools for teacher retirement events and to assess its alignment with principles of transparency, accountability, and financial governance as mandated by educational management theory and national regulations. Methodology: This research employs a qualitative document-analysis approach. Data were obtained from online news sources, government regulations, and academic literature on school financial management. Main findings: The findings reveal that the Rp50,000 student levy lacked formal planning, was not included in the school budgeting document (RKAS), was conducted without school committee approval, and had no official financial reporting. These conditions indicate violations of transparency, fairness, and school accountability principles. Applications of this study: The study offers insights useful for improving school financial policies, strengthening public fund supervision, enhancing educational management practices, and reforming financial governance within educational institutions. Novelty/Originality: This study presents an integrated analysis combining management theory, regulatory frameworks, and real-life case evidence, offering new perspectives on how informal levies affect school governance systems and public trust.